Bentuk Dan Fungsi Ragam Hias Pada Pendapa Sasana Sewaka Di Keraton Kasunanan Surakarta joko Budiwiyanto - joko Budiwiyanto (Institut Seni Indonesia Surakarta, 2007)
This Article represent result of conducted by research at Sasana Sewaka pendapa in Keraton Surakarta. used by Type Research is qualitative by using approach of hermeneutik. From result of analysis can be conduded, that classified decorative manner form to become geometric form, flora, fauna, calligraphy, and other jorms. location of decorative Manner, classified to become two, that is decorative manner which have the character of constructive and decorative manner which have the character of patching. Function from decorative manner is as building element decorator, sacral function symbolic, and social junctionKeyword: Form, Function, Decorative Manner.